Change in student beliefs about attitudes toward science in grades 6-9 - (:unkn) unknown (My University, 2010)
The study reports on an investigation of the impact of a Science-Technology-Society (STS) approach in promoting more positive student attitudes toward science that are recommended by current reform documents. A total of 609 students from grades six through nine were selected for a survey of attitudes in two class sections assigned as either experimental (STS oriented class) or control group (textbook oriented class). The results indicate that students in classes taught with an STS approach develop more positive attitudes toward science when compared to students in classes taught with a textbook-oriented approach. The STS approach to science teaching works equally well for male and female students regarding student attitudes toward science. Significant differences were not found between male and female students in terms of improving positive attitudes concerning science study. © 2010 HKIEd APFSLT.